Post-deployment Mental Health in Reserve and National Guard Service Members: Deploying With or Without One’s Unit and Deployment Preparedness - Ursano, Robert J (Mil Med, 2018)
BACKGROUND: Given the greater prevalence of post-deployment mental health concerns among reservists, the higher likelihood of deploying without their regular unit, and potentially lower rates of deployment preparedness, we examined associations between deploying with or without one’s regular unit (individual augmentee status, IAS), deployment preparedness, and mental health problems including post-traumatic stress disorder (PTSD), depression (MDD), and binge drinking in a nationally representative sample of Reserve Component (RC) Army and Marine-enlisted males (n = 705). METHODS: A series of multivariate regressions examined the association of mental health with IAS and deployment preparedness, adjusting for demographics. To examine whether deployment preparedness varied by IAS, an IAS × deployment preparedness interaction was included. FINDINGS: In an adjusted model, being an individual augmentee and low deployment preparedness were associated with any mental health problem (screening positive for PTSD, MDD, binge drinking, or any combination of the three). There was a significant IAS × deployment preparedness interaction. Mental health problems did not vary by preparedness among individual augmentees. Participants deploying with regular units with low–medium preparedness had greater risk for mental health problems (odds ratio [OR] = 3.69, 95% confidence interval [CI] = 1.78–7.62 and OR = 2.29, 95% CI = 1.12–4.71), than those with high preparedness. RC-enlisted male personnel who deployed without their regular unit were five times more likely to have a mental health problem, and were 61% more likely to report binge drinking. Additionally, those with lower levels of deployment preparedness were up to three times more likely to have a mental health problem and up to six times more likely to report PTSD. DISCUSSION: The current investigation found that both IAS and deployment preparedness were associated with negative mental health outcomes in a large representative sample of previously deployed RC-enlisted male personnel. In particular, low deployment preparedness was associated with an increased likelihood of PTSD, and deploying without one’s regular unit was associated with increased rates of binge drinking. There were also significant main and interaction effects of IAS and deployment preparedness on having a mental health problem. It is possible that limiting the number of RC personnel deploying without their regular unit may help to decrease alcohol misuse among U.S. Armed Services reservists during and after future conflicts. Also, to the extent that deployment preparedness is a modifiable risk factor, future studies should examine whether increasing deployment preparedness could mitigate some of the correlates of deployment-related trauma exposure. Finally, future investigation is needed to explain why those who deploy without their regular unit, but who report high deployment preparedness, remain at elevated risk for mental health problems. It is possible that individual augmentees can benefit from a specific preparation for deployment. Those deploying without their regular unit had higher rates of mental health problems regardless of preparedness. These findings have implications for deployment preparedness training for those deploying without their regular unit.